Profile of Patients with Decreased Bone Density Aged Over 50 Years Old with Cases of Femoral Neck Fracture, Thoracic Vertebral Compression Fracture, Lumbar Vertebral Compression Fracture, and Distal Radius Fracture in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, in 2019-2020 - Pratama, Arlingga; Sari, Gadis Meinar; Utomo, Dwikora Novembri (Universitas Airlangga, 2025)
Highlights: Decreased bone density often progresses to osteoporosis, where osteoporosis is a degenerative disease characterized by low bone mass, bone tissue damage, and bone microarchitecture disorders that can lead to an increased risk of bone fracture. Fractures often found in low bone density consist of fractures of the femoral neck, the thoracic and lumbar vertebrae, and distal radius fractures. Abstract Introduction: Human life expectancy will increase over time, as will various chronic degenerative diseases, one of which is fracture caused by decreased bone mass density. This study described fracture features associated with decreased bone mass density in patients over 50 years old. Methods: This study took place at the Polyclinic of Orthopaedics and Traumatology Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, using a quantitative design with a cross-sectional approach. The sample in this study consisted of 56 medical records collected using a questionnaire processed with Microsoft Excel. Results: This study used 56 samples. Femoral neck fractures had the highest number of decreased bone mass density fractures (69.7%). The most common body mass index (BMI) found with fractures was obese patients (32.2%). Most fractures were experienced by females (64.3%). The location of the highest incidence of fractures was found in domestic accidents (66.1%) with low-energy trauma (67.9%). Conclusion: Most of the fractures caused by decreased bone density in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, were femoral neck fractures, with females being the most common gender. These fractures were also the most common in obese patients, and the highest incidence was found in domestic accidents with low-energy trauma.